Megalencephaly Capillary Malformation Syndrome - Praticò, Andrea D.; Polizzi, Agata; Salafia, Stefania; Praticò, Elena R.; Garozzo, Maria Teresa; Sullo, Federica; Catanzaro, Stefano; Belfiore, Giuseppe; Pirrone, Concetta; Zanghì, Antonio; Fiumara, Agata; Ruggieri, Martino; Resta, Nicoletta (Journal of Pediatric Neurology, 2018)
Megalencephaly capillary malformation polymicrogyria (MCAP) syndrome is characterized by the sporadic occurrence of congenital and progressive megalencephaly, brain malformations including polymicrogyria, pre- and postnatal overgrowth with body asymmetry, cutaneous vascular malformations (including capillary malformation and cutis marmorata), digital anomalies connective tissue dysplasia (including skin and joint laxity), and developmental delay. In the past 10 years, the specific cause of the disease has been found in gain-of-function mutations of PIK3CA gene, mostly somatic/postzygotic but in rare cases also de novo germline. Such gene encodes for PI3K, a critical member of the PI3K-AKT-mTOR pathway: genetic changes lead to an over-activation of this signaling system, with increased vascular, limb, and brain cell development, progression, and survival. Interestingly, mutations in the same gene can cause other clinically heterogeneous syndromes, including CLOVE syndrome, macrodactyly, focal adipose overgrowth, epidermal nevi, facial infiltrating lipomatosis: all these syndromes (even if heterogeneous) are now considered a unique spectrum, known as PIK3CA-related overgrowth syndrome. On the contrary, a disease strictly similar to MCAP, characterized by megalencephaly, polymicrogyria, polydactyly, and hydrocephalus has been found to be caused by mutations in two other PI3K-AKT-mTOR-releted genes, AKT3 and PIK3R2, and for this reason is not included in the upper mentioned group of syndromes. With the exception of neurosurgery strategies for hydrocephalus and posterior fossa overcrowding, therapeutic options are nowadays limited, even if gene-targeted treatment protocols have been proposed and protocols with such agents (i.e., Arq092) are currently ongoing in small groups of patients with promising results.
Keywords: megalencephaly; polymicrogyria; capillary malformations; hydrocephalus; AKT-PI3K-mTOR; developmental delay